ANALISI TINGKAT PEMAHAMAN MASYARAKAT DESA RANTO NATAS TERHADAP BAYAHA NARKOBA, JUDI ONLINE, DAN PINJAMAN ONLINE - Ridwanda Sapikri; Risna Handayani; Nanda Fitri; Riska Melinda; Asmin Hamid; Wardah Rangkuti; Siti Arfah Lubis; Irham Akasyah; Khodma Siah; Liantha Adam Nasution; Syarifah Syarifah (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the level of public understanding in Ranto Natas Village regarding the dangers of drugs, online gambling, and online loans, which have become pressing issues in Indonesia. The research employed a qualitative method through literature review and field observation. The findings indicate that most villagers demonstrate a relatively high awareness of these threats, supported by the roles of religious leaders, community figures, village authorities, and educational programs such as the KKN STAIN Madina. Nevertheless, a small portion of residents remain vulnerable, particularly to drug abuse and online gambling, driven by economic hardship, low education, weak family supervision, and extensive access to technology. This study contributes to strengthening preventive strategies through community-based education, digital literacy, and family involvement to safeguard young generations from the adverse impacts of drugs, online gambling, and illegal online loans.